Flow field analysis of a twin impeller fan - Sim, Kian Hui (Nanyang Technological University, 2021)
The application of the twin impeller fan is commonly used in the ventilation of underground tunnels and it normally operates for 24 hours per day. It is essential to optimise the efficiency of the twin impeller fan in order to reduce the energy consumption rate and thus the cost to operate it. In collaboration with Mason industries, this study is an advancement of the previous work, and aims to optimise the fan by changing the design of the machine casing. The focus for this study is on the different angle of guide vanes and how it would affect the flow of air through the fan. Optimal angle would also be obtained by comparing the pressure performance. Computational Fluid Dynamics (CFD) software, in particular Ansys Fluent would be used to conduct simulations on the study as it reduces the time taken and cost, as compared to the use of traditional methods in creating prototypes and running experiments physically. Once simulations are completed, results would be collated and analysed. Fan curves would be generated for verification of results obtained and provides a clear visual for comparison of the pressure performance. This is to obtain the optimal angle of guide vanes. Streamlines were produced as well to analyse the flow of air through the various angle of guide vanes. The results of the fan curves showed some inconsistency, for instance there were overlapping of fan curves for the different angles of guide vanes and fluctuations in pressure within a fan curve. Further investigations were done to determine the cause of these inconsistencies and explanation would be provided in the study. The investigation of inconsistencies was focused on the mesh element size, simulation model and comparison with various research articles. It was concluded that the optimal angle of guide vanes to be 80° for volume flow rate of less than 20000 m3/h. The streamlines of air in the guide vanes can be categorised into three groups: air flow not affected by guide vanes, air flow smoothened by guide vanes, and air flow disrupted by guide vanes. It was discovered that when the angle of guide vanes increases past 90 degrees angle, the amount of disrupted air flow increased as well. The fluctuations within a fan curve could be reduced by using a smaller mesh size to increase the accuracy of the results. A different simulation model, the sliding mesh model, can be used to simulate for better accuracy and verify if the optimal angle of guide vanes is the same at higher flow rates. The overlapping of fan curves may be due to the novelty of the study itself and should not be considered as an “inconsistency”. This is with reference to another research article which simulates the change in blade angles. However, future investigations should be carried out to verify it.